2014
DOI: 10.1016/j.biomaterials.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and enrichment of CD133+ glioblastoma cancer stem cells on 3D chitosan-alginate scaffolds

Abstract: Emerging evidence implicates cancer stem cells (CSCs) as primary determinants of the clinical behavior of human cancers, representing an ideal target for next-generation anticancer therapies. However CSCs are difficult to propagate in vitro, severely limiting the study of CSC biology and drug development. Here we report that growing cells from glioblastoma (GBM) cell lines on three dimensional (3D) porous chitosan-alginate (CA) scaffolds dramatically promotes the proliferation and enrichment of cells possessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 33 publications
5
85
0
1
Order By: Relevance
“…These results indicate that 3D collagen scaffolds may provide a useful platform for anti-cancer therapeutics and CSC research. Furthermore, breast cancer stem cell expansion in PCL scaffolds (83), ovarian cancer stem cell behavior and drug resistance investigated in 3D basement membrane extract scaffolds (84) and glioma stem cells proliferating in 3D chitosan-alginate scaffolds (85) were observed in these studies, sequentially.…”
Section: Multicellular Tumor Spheroids (Mcts)mentioning
confidence: 99%
“…These results indicate that 3D collagen scaffolds may provide a useful platform for anti-cancer therapeutics and CSC research. Furthermore, breast cancer stem cell expansion in PCL scaffolds (83), ovarian cancer stem cell behavior and drug resistance investigated in 3D basement membrane extract scaffolds (84) and glioma stem cells proliferating in 3D chitosan-alginate scaffolds (85) were observed in these studies, sequentially.…”
Section: Multicellular Tumor Spheroids (Mcts)mentioning
confidence: 99%
“…49 In a follow-up study, the authors demonstrated that chitosan-alginate scaffolds promoted the growth and enrichment of the CD133 + CSC population in glioblastoma cells and that the microenvironment provided by the scaffolds contributed to the more stem-like state of the cells through CD44 (a CSC marker) signaling and EMT. 15 Lastly, chitosan-alginate scaffolds have also been used to culture liver cancer cell, namely hepatocellular carcinoma (HCC), with similar results: HCC cells grown in 3D scaffolds featured greater angiogenic potential, increased expression of markers for malignancy and migration, rapid transfer into animals, and an increased resistance to chemotherapy in comparison to 2D cultures. 50 Another natural material being explored as a scaffold for cancer cells and CSC enrichment is hyaluronan (HA).…”
Section: Biomaterials For Csc Growthmentioning
confidence: 97%
“…13 Unfortunately, CSCs are difficult to propagate in vitro due to the difficulty of recapitulating the necessary CSC niche, 14 which severely limits the study of CSC biology as well as therapy development. 15 Typically, CSCs are propagated and studied in vivo or in tumor spheroid models grown on non-adhesive substrates and serum-free media. 16 Here, we suggest that improved cancer models will further support CSC enrichment and that such in vitro models will include clever biomaterial designs.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, a de-acetylated product of chitin, is a biocompatible polysaccharide (Hari & Nair, 2016;Rodrigues, Dionísio, Remuñán López, Grenha, 2012;Ravindranathan, Koppolu, Smith, Zaharoff, 2016) with a number of biomedical applications such as wound dressing (Anithaa, Sowmyaa & Sudheesh, 2014;Archana, Singh, Dutta & Dutta, 2015;Dina & Sahl, 2009;Dutta & Dutta, 2015;Harkins, Duri, Kloth & Tran, 2014;Keong & Halim, 2009), drug delivery (Gowda et al, 2015;Tajmir-Riahi, NafisiSh, Sanyakamdhorn & Agudelo et al, 2014), tissue re-generation, artificial cartilage (Nettles, Elder, Gilbert, 2002;Gowda et al, 2015;Tajmir-Riahi, NafisiSh, Sanyakamdhorn & Agudelo et al, 2014), porous scaffolds (Ahmed et al, 2015;Baniasadi, Ramazani & Mashayekhan, 2014;Kievit et al, 2014;Rahman, Pervez, Mubarak, Khan, 2013) etc. Chitosan, due to its cationic nature in the dissolved state, has also been exploited to prepare its IPC matrix with appropriate anionic polymers for various biomedical applications (Sakloetsakun, Preechagoon, Bernkop-Schnürch & Pongjanyakul, 2016;Kassem, Ismail, Naggar, & Aboulmagd, 2015;Argin, Kofinas & Lo, 2014).…”
Section: Introductionmentioning
confidence: 98%